Drug Delivery: Engineering the Surface of Smart Nanocarriers Using a pH‐/Thermal‐/GSH‐Responsive Polymer Zipper for Precise Tumor Targeting Therapy In Vivo (Adv. Mater. 36/2017). Issue 36 (21st September 2017) - Zhang, Penghui; Wang, Yan; Lian, Jing; Shen, Qi; Wang, Chen; Ma, Bohan; Zhang, Yuchao; Xu, Tingting; Li, Jianxin; Shao, Yongping; Xu, Feng; Zhu, Jun‐Jie
Abstract : In article number1702311, Feng Xu, Jun‐Jie Zhu, and co‐workers tune nanocarrier surface compositions on command for precise tumor targeting by way of pH‐/thermal‐/glutathione‐responsive polymer zippers. The nanocarriers remain stealthy during blood circulation, but their surfaces are activated by the acidic microenvironment and photothermal heating at tumor sites for enhanced cellular uptake and efficient drug release.